2010
DOI: 10.1073/pnas.1002894107
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of HIV-1 latency in resting CD4 + T cells depends on chemokine-induced changes in the actin cytoskeleton

Abstract: Eradication of HIV-1 with highly active antiretroviral therapy (HAART) is not possible due to the persistence of long-lived, latently infected resting memory CD4 + T cells. We now show that HIV-1 latency can be established in resting CD4+ T cells infected with HIV-1 after exposure to ligands for CCR7 (CCL19), CXCR3 (CXCL9 and CXCL10), and CCR6 (CCL20) but not in unactivated CD4 + T cells. The mechanism did not involve cell activation or significant changes in gene expression, but was associated with rapid deph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
256
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(284 citation statements)
references
References 57 publications
21
256
2
Order By: Relevance
“…In vivo HIV-1 latency is thought to be predominantly established by the return of a productively infected activated CD4 + cell to a resting memory state (20). Alternatively, preactivation latency has also been described, where HIV-1 DNA can be integrated into quiescent rCD4 cells via interactions of chemokines with CCR7, CXCR3, and CCR6 in the absence of productive infection (21). Independently of whether productive infection has occurred, the G 0 resting state in rCD4 cells contributes to the inhibition of HIV-1 transcription and translation through a variety of mechanisms, including the sequestration of transcription factors NF-κB and NFAT (22,23); association of P-TEFb with the inhibitory 7SK snRNA complex (24,25); and association of the BAF complex and histone deacetylases with the HIV long terminal repeat (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo HIV-1 latency is thought to be predominantly established by the return of a productively infected activated CD4 + cell to a resting memory state (20). Alternatively, preactivation latency has also been described, where HIV-1 DNA can be integrated into quiescent rCD4 cells via interactions of chemokines with CCR7, CXCR3, and CCR6 in the absence of productive infection (21). Independently of whether productive infection has occurred, the G 0 resting state in rCD4 cells contributes to the inhibition of HIV-1 transcription and translation through a variety of mechanisms, including the sequestration of transcription factors NF-κB and NFAT (22,23); association of P-TEFb with the inhibitory 7SK snRNA complex (24,25); and association of the BAF complex and histone deacetylases with the HIV long terminal repeat (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…This led us to speculate that the cortical actin may be a factor affecting HIV infection of memory and naive CD4 T cells. Indeed, recent studies have demonstrated that the cortical actin is involved in HIV entry, DNA synthesis, and nuclear migration and is required for the establishment of HIV latent infection of resting CD4 T cells (22)(23)(24)(25)(26). To substantiate this speculation, we examined the cortical actin density in resting CD4 T cells from 68 healthy donors.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…T cell migration is mainly driven by cortical actin polymerization mediated by actin regulators such as Arp2/3 and cofilin, which are downstream effectors of chemokine receptor signaling (20). The cortical actin is also a major determinant of T cell susceptibility to viral pathogens such as HIV-1 (21)(22)(23)(24)(25)(26). During HIV infection of resting CD4 T cells, the virus utilizes the envelope protein to interact with the chemokine coreceptor to trigger cofilin activation and actin dynamics, mimicking the chemotactic process to facilitate viral entry, DNA synthesis, and intracellular migration (22)(23)(24)27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study established that CCL20, along with other chemokines, was able to facilitate efficient HIV-1 integration in resting CD4 + T cells by binding to CCR6 displayed on these cells. This occurred independently of cell activation and was likely achieved by the rearrangement of the cytoskeleton that facilitated effective transportation of the virus into the nucleus [67]. Because most CD4 + CCR6 + cells are T H 17 or T H 17-like cells, this is a possible mechanism by which these cells become targeted by the virus and latency established.…”
Section: Ccl20 In Viral Pathogenesis and Immunitymentioning
confidence: 99%